Polyphyllin I Inhibits Proliferation and Induces Apoptosis by Downregulating AML1‐ETO and Suppressing C‐KIT/Akt Signaling in t(8;21) Acute Myeloid Leukemia. Issue 11 (26th October 2018) - Chai, Yanting; Si, Ying; Xu, Jiaxin; Xiang, Yuchen; Zhao, Hongyan; Si, Yuan; Zhang, Te; Liu, Ying
Abstract: Polyphyllin I (PPI), a bioactive constituent extracted from traditional medicinal herbs, is cytotoxic to several cancer types. However, whether PPI can be used to treat t(8;21) acute myeloid leukemia (AML) cells requires further investigation. Here, we determined the inhibitory effects of PPI on t(8;21) AML cells by Cell Counting Kit‐8 (CCK‐8) and the trypan blue dye exclusion assay. DAPI staining and Wright–Giemsa staining were performed to check for apoptosis. Detection of apoptotic protein and AML1‐ETO signaling protein expression were conducted by Western blot analysis. Our results suggested that PPI decreased growth and induced apoptosis in a dosage‐dependent manner in the t(8;21) AML cell line Kasumi‐1. PPI significantly downregulated AML1‐ETO expression in a dosage‐ and time‐dependent manner. PPI also upregulated P21 and downregulated survivin expression by reducing AML1‐ETO. Mechanistically, PPI significantly reduced the expression of C‐KIT, another therapeutic target for AML with t(8;21), followed by inhibition of Akt signaling. These results suggest that PPI can suppress growth and induce apoptosis of t(8;21) AML by suppressing the AML1‐ETO and C‐KIT/Akt signaling pathways. Therefore, PPI may be an anticancer therapeutic to treat t(8;21) AML. Abstract :